2017
DOI: 10.1186/s12970-017-0170-2
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition practices and knowledge among NCAA Division III football players

Abstract: BackgroundParticipation in collegiate American football is physically demanding and may have long-term health implications, particularly in relation to cardiovascular and neurological health. National Collegiate Athletic Association (NCAA) Division III (DIII) football players are a relatively unstudied population, particularly in terms of their dietary habits and knowledge. The aim of the present study was to descriptively evaluate the dietary intake of DIII football players including a subset of linemen and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
79
4
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(96 citation statements)
references
References 40 publications
9
79
4
4
Order By: Relevance
“…While many respondents (48%) reported that they had been previously given diet advice from their coach or trainer, only 2% of athletes actually selected “coach” their most preferred source of nutrition information. This is in contrast to existing international reports, which found that American college athletes were more likely to seek advice from a trainer or coach than a dietitian, and felt more comfortable discussing their nutritional needs with their trainer, coach, parent or friend than with a dietitian. These differences may be reflective of varying roles of a sporting coach in an Australian and international context.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…While many respondents (48%) reported that they had been previously given diet advice from their coach or trainer, only 2% of athletes actually selected “coach” their most preferred source of nutrition information. This is in contrast to existing international reports, which found that American college athletes were more likely to seek advice from a trainer or coach than a dietitian, and felt more comfortable discussing their nutritional needs with their trainer, coach, parent or friend than with a dietitian. These differences may be reflective of varying roles of a sporting coach in an Australian and international context.…”
Section: Discussioncontrasting
confidence: 99%
“…Studies that have evaluated American collegiate athletes' preferred nutrition information sources have reported mixed findings; including that athletes are most likely to seek information from a strength and conditioning coach, 9 a physician, 10 the media and the internet, 10 their parents and family, 11 an athletic trainer, 12 and their coach. 13 Indian college athletes preferred obtaining nutrition information from their parents, 14 while Iranian 14 and Nigerian 15 athletes were most likely to obtain nutrition information from their coaches. To our knowledge, only three studies in Australian athletes have assessed preferred sources of information.…”
Section: Introductionmentioning
confidence: 99%
“…However, sweat rates influencing sodium loss can differ broadly among individuals. Hence, considering each athlete's unique physiological needs, guidelines for sodium intake should be established (Abbey, Wright, Christina, & Kirkpatrick, 2017). A research finding suggested that dietary fibre enhances athletic performance, reduces physical stress, and augments the normal diurnal changes in cortisol levels (Sugiyama, Yamaguchi, Hu, A. Kobayashi, & H. Kobayashi, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, based on the correct response of the nutrition knowledge and practice score, the study participants exhibited a relatively low level of nutrition knowledge and practice compared to previous ndings, a study conducted by Folasire OF et al (2015) and Abbey et al (2017), where less than half (42.8%) and (35%) had poor nutritional knowledge [20,27]. However, our result is in line with the other studies report where overall nutrition knowledge scores were low [9,28].…”
Section: Discussionmentioning
confidence: 67%